Exploring Higher Order Risk Effects - DECK, CARY; SCHLESINGER, HARRIS (Review of Economic Studies, 2010)
Precautionary saving has been linked to the property of prudence, and the property of temperance has been used to show how the presence of an unavoidable risk affects one's behaviour towards a second risk. These two higher order risk effects also play key roles in aversion to negative skewness and to kurtosis, respectively. This article presents a laboratory experiment to determine whether subjects are prudent and/or temperate. The experiment is based upon preferences over lottery pairs in simple 50–50 gambles. Subjects are asked in which of two states of nature they would prefer to receive a zero-mean gamble. For prudence, the choices are between a lower and higher wealth outcome. For temperance, the choices are between a state with no other risk and a state with a second (independent) risk. The results show behavioural evidence for prudence, but they also show evidence of intemperate behaviour. Implications of these results for both expected-utility and non-expected-utility models are examined.